Mentioning of the Righteous and the Wicked in Surat Al-Mutaffifin in the Quran; An Analytical Rhetorical Study - Al-Osaimi, Meshal Fehan Ballash (Arab Journal for Sciences and Research Publishing, 2023)
The research aims to investigate Surat Al-Mutaffifin, which consists of thirty-six verses, rhetorically and analytically, in an attempt to answer some pressing questions as follows; how can studying Surat Al-Mutaffifin rhetorically answer questions like: why is an entire Quranic Chapter dedicated to fraudulency in (weighing and measuring)? What is the true meaning of fraudulency? What is the reality of the wicked and the righteous in this worldly life? What is the secret of balancing between them in Al-Mutaffifin Chapter by talking about fraudulency in (weighing and measuring) as a major sin? And why are there multiple names of the people of hell in the Chapter like in (the fraudulent, the wicked, the liars, the criminals, the infidels)? Is there a worldly or eschatological relationship between them? Or are they - all - names for the doer of that sin? How does the eloquence of the Qur’anic text in the Chapter achieve the goals of promising and threatening? Is there a major sin that brings a Muslim out of faith to unbelief other than associating others with Almighty God? And how the eloquence of the Qur’anic text became a faithful messenger, that delivers spiritual, psychological, and intellectual messages; for all those to whom the Qur’anic discourse is addressed, not just abstract arts and ornaments that are meant for themselves?The research, also, attempts to confirm that the Qur’anic rhetoric is a representation of the same meanings, so it is not possible to separate - in any way - between the scope of meanings and that of rhetoric because when practicing analysis there are no spaces separating them, both of them are intermingled and united, and extends to include all the Qur’anic text completely, when the analytical practice of a particular verse extends those scopes, and extends to the rest of the total text, detailing the general, or revealing the ambiguous, in operations of parallelism, intersection, and integration, which filters one interpretation, or displaces another, or combines between a number of interpretations under the umbrella of textual probability; encompassing the other textual processes that reveal intermingling and integration of both scopes, in an effort to form more mature interpretations when this practice becomes active.
Keywords: the righteous; the wicked; the fraudulent (in weighing and measuring)